Clonality of CD4+ Blood T Cells Predicts Longer Survival With CTLA4 or PD-1 Checkpoint Inhibition in Advanced Melanoma - Arakawa, Akiko; Vollmer, Sigrid; Tietze, Julia; Galinski, Adrian; Heppt, Markus V.; Bürdek, Maja; Berking, Carola; Prinz, Jörg C. (Frontiers in Immunology, 2019)
Recognition of cancer antigens drives the clonal expansion of cancer-reactive T cells, which is thought to contribute to restricted T-cell receptor (TCR) repertoires in tumor-infiltrating lymphocytes (TILs). To understand how tumors escape anti-tumor immunity, we investigated tumor-associated T-cell repertoires of patients with advanced melanoma and after blockade of the cytotoxic T-lymphocyte-associated protein 4 (CTLA4) or programmed cell death 1 (PD-1). TCR Vβ-gene spectratyping allowed us to quantify restrictions of T-cell repertoires and, further, diversities of T-cell clones. In this study, we show that the blood TCR repertoires were variably restricted in CD4+ and extensively restricted in CD8+ T cells of patients with advanced melanoma, and contained clones in both T-cell fractions prior to the start of immunotherapy. A greater diversification especially of CD4+ blood T-cell clones before immunotherapy showed statistically significant correlations with long-term survival upon CTLA4 or PD-1 inhibition. Analysis of TILs and corresponding blood available in one patient indicated that blood clonality may at least partially be related to the clonal expansion in the tumor microenvironment. In patients who developed severe immune-related adverse events (IrAEs), CD4+ and CD8+ TCR spectratypes became more restricted during anti-CTLA4 treatment, suggesting that newly expanded oligoclonal T-cell responses may contribute to IrAEs. This study reveals diverse T-cell clones in the blood of melanoma patients prior to immunotherapy, which may reflect the extent to which T cells are able to react against melanoma and potentially control melanoma progression. Therefore the T-cell clonality in the circulation may have predictive value for antitumor responses from checkpoint inhibition.